Speak out!: Authentic communication activities for the intermediate & advance ESL student - Measday, Ellen; Knight, Lisa F. (Dubuque : Kendall Hunt Publishing Company, 2006)
The object of this book is to generate spoken language from students on a wide variety of topics that are based in American culture. It is designed for intermediate to advanced speakers of English who need continued work to further develop their fluency in English. Using Speak Out! will aid teachers in promotion speaking skills both inside and outside of the classroom with fellow students an native-speakers of English. It promotes active learning and critical thinking skil by requiring students to research and plan their own oral presentations. For th reason, we have tried to provide support for the students while leaving enou room for them to create their presentations themselves. Speak Out! is designed to be teacher-friendly in its organization and focus. Ea unit has a grammar focus which is listed in the table of contents and will teachers who want to integrate some grammar topics into the activities. In addition, the activities are organized into groups that can be taught in different t slots. Whether you need an activity that will take twenty minutes or all same you will have many to choose from in Speak Out!
1. To Tell the Truth -- 2. Make-a-Date -- 3. Getting to Know You -- 4. Zoo -- 5. Secret Phrases -- 6. Euphemisms -- 7. Leisure Activities -- 8. Pets -- 9. You Took the Words Right Out of My Mouth -- 10. Treasure Hunt -- 11. Aging Parents -- 12. Exercise and Fitness -- 13. Taking Risks -- 14. Compliments -- 15. Advice Column.
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE